Needs analysis of soft skills psychoeducational intervention module among aggresive adolescents - Amat, Salleh; Ali, Alida; Mahmud, Mohd Izwan; Puad Mohd Kari, Dharatun Nissa; Abu Bakar, Abu Yazid; Mohd Ismail, Zarina Mizam; Ku Johari, Ku Suhaila; Kamarulzaman, Mohd Hasrul (Gokmen Arslan, 2022)
This article discusses a needs analysis study conducted for the construction and development of a relevant, comprehensive and holistic training module, namely the Soft Skills Psychoeducational Intervention Module (SSPIM) that measures the perception of aggressive adolescents in one moral rehabilitation school in Kuala Lumpur. This study also identifies the relevant life skills elements to be included in SSPIM. This needs analysis employed a survey study design utilizing WHO’s core life skills framework. A set of research questionnaires was distributed to a total of 94 male adolescent trainees aged between 15 and 17 years and behaving aggressively. The overall analysis revealed a high-level mean score of 3.91 indicating that there is a need for the inclusion of WHO’s core life skills framework as a sub-scale in SSPIM in order to improve life skills and resilience and reduce adolescent aggressive behavior. The development of SSPIM is indeed beneficial and can be implemented by stakeholders for the aggressive adolescents in moral rehabilitation schools through psycho-educational group interventions.